Acts and Laws of His Majesty's Province of New Hampshire in New England 115-16 (1761) - (:unkn) unknown (My University, 1759)
An Act in Addition to the Act for Regulating the Militia: No person or persons whatever in any town or garrison within this province, shall during the time of war, or of keeping a military watch in such town or garrison, presume to discharge or shoot off any gun or guns after sun-setting, or before the sun's-rising
Keywords: DISCHARGE